Switchgrass Harvest Time Management Can Impact Biomass Yield and Nutrient Content. Issue 4 (1st July 2016) - Serapiglia, Michelle J.; Boateng, Akwasi A.; Lee, D.K.; Casler, Michael D.
Abstract : Switchgrass ( Panicum virgatum L.) is a dedicated energy crop native to tallgrass prairie and savanna ecosystems of North America. Although high biomass yield is of significant importance for the development of switchgrass as a bioenergy crop, mineral nutrients in biomass are critically important for sustainable bioenergy crop production but are detrimental for thermochemical conversion of biomass to energy. To evaluate biomass yield and nutrient uptake or nutrient cycling in switchgrass cultivars, replicated trials across three sites (Arlington, WI; Marshfield, WI; and Urbana, IL) were established in 2009. The switchgrass cultivars were harvested once annually at upland peak, after killing frost, or post‐winter in the spring from 2010 to 2014. Switchgrass biomass yield was greatest at the upland peak harvest, averaging 9.9 Mg ha −1 with biomass decreasing as harvest was delayed. Similarly, nutrient content in the biomass was greatest at the upland peak harvest with N, P, and K at 69, 77, and 23 kg ha −1, respectively. The majority of the N, P, and K in the biomass at the upland peak harvest was absent from the biomass at the post‐frost harvest. The lower levels of nutrients and total ash in the biomass at the post‐frost harvests will be beneficial for downstream conversion to bioenergy and may also reduce the future fertilizer requirements of the biomass crop.